Effects of the U.S. Banking Crisis in 2008: Evidence from International Stock Markets - Toivonen, Lassi (My University, 2009)
The purpose of this thesis is to compare returns and volatilities of regionally constructed market portfolios before and after three major economic events related to the banking crisis in the U.S. in 2008. The selected events are the acquisition of investment bank Bear Stearns on the 16th of March 2008, the announcement of the U.S. government acquisition of two major mortgage associations (Fannie Mae and Freddie Mac) on the 7th of September 2008 and the liquidation of investment bank Lehman Brothers on the 15th of September 2008. The event window for this study is 1 week, 1 month and 3 months before and after the events. This thesis provides results about the behaviour of international stock markets during this crisis and is likely to be in the front line of the forthcoming article flood considering this crisis. An international comparison is made between 6 regional market portfolios. These portfolios are Europe, Asia, Eastern Europe, G8 countries, Latin America and the Middle East and North Africa (MENA). These portfolios include a total of 53 different national stock market indices. The impact of these three major economic events is calculated using a paired comparison between each pair of portfolios and through individual comparison of regions. This thesis finds that the effect of the events of Fannie Mae, Freddie Mac and Lehman Brothers have a more significant effect to stock returns and volatilities than the events of Bear Stearns had. It seems that developed G8 countries had partly higher longterm volatilities after the events of Fannie Mae, Freddie Mac and Lehman Brothers suggesting that the crisis affected most significantly to the volatilities of these developed countries. However, this thesis is able to find that all the regions showed significantly higher volatilities after the events of Fannie Mae, Freddie Mac and Lehman Brothers when compared to the time period before the events in question. There rise also evidence that in the long-run almost all regions had negative change in returns after the events of Fannie Mae, Freddie Mac and Lehman Brothers.
Keywords: financial crisis; shock; market portfolio; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|